THE RURAL-URBAN GAP AND THE POLICY RESPONSE: A STUDY OF POST-INDEPENDENCE INDIA - Hassan, Mofidul (International Journal of Research -GRANTHAALAYAH, 2016)
The rural-urban gap in development attainment has attracted the attention of many economists. Lewis, Fei-Ranis, and Harish-Todaro models focus on the rural-urban dualism in underdeveloped economies and proceed to illustrate how the economies get transformed in the process of development. When India attained independence in 1947, it was a predominantly rural, agricultural and colonially exploited poor country. During the last seven decades of development effort the country have achieved many heights and got slowly but steadily urbanized. In an attempt to bridge the rural urban gaps in development attainment, Government’s rural development policies got continuously evolved during this period. The present paper traces the changing phased of policy of rural development in Independent India and examines the outcomes of these policies in terms of the trends in the rural-urban disparities in some key development indicators. The study shows a distinct sign of reduction in the disparity over the years.